Reductive nanometric patterning of graphene oxide paper using electron beam lithography - Gonçalves, Gil (2018)
Electron beam lithography (EBL) was used for preparing nanostructured reduced patterns on the GO paper surface, while preserving its mechanical resistance and flexibility. Different EBL parameters, like dose and time of exposure for patterning were tested. SEM analysis showed the consequent increase of contrast of the reduced stripes on the patterned regions due to the increase of electron beam doses. Moreover, surface potential microscopy experiments also exhibited a clear contrast between the patterned and non-patterned regions. Structural analysis of the patterned paper through X-ray diffraction and nanoindentation showed that the interlayer distance between GO sheets decreases after reduction allowing the increase of the Hardness and Young modulus that makes this material able to be manipulated and integrated on different devices. Furthermore, we also observe that exposed areas to electron beam reduction process show an increase in the electrical conductivity up to 3 × 104 times. The developed flexible GO films can have interesting applications such as biosensors or templates for inducing tissue regeneration, by providing a surface with differently patterned cues with contrasting electron mobility. Preliminary in vitro studies with L929 fibroblasts support the cytocompatible nature of this patterned GO paper.